EFEKTIVITAS PEMUNGUTAN PAJAK REKLAME DAN KONTRIBUSINYA TERHADAP PAJAK DAERAH (Studi pada Badan Pendapatan Daerah Kabupaten Malang Tahun 2019-2021) - Perdana, Rizky Nurhidayat; Said, M. Mas'ud; Musa, Ali Masykur (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The decentralization system implemented in the Indonesian government makes each region obliged to finance its own regional households for the implementation of regional autonomy that is able to realize regional independence and equitable development to improve people's welfare. The government tries to finance its own work program by optimizing local revenue, one of which is from the local tax sector, namely billboard tax. The purpose of this study is to solve the problem of how the Malang Regency Government can collect billboard tax effectively and efficiently according to the potential existing billboard tax revenue target, so that it can be seen to what extent billboard tax collection can contribute to local tax revenue in Malang Regency. The performance of the Malang Regency government in implementing billboard tax collection is explored more deeply in this study, which uses an analytical descriptive method with a qualitative approach. Data collection methods include observation, documentation, and interviews. The data analysis method used qualitative analysis procedures. The research findings show that for three years from 2019 to 2021, the effectiveness of Malang Regency's billboard tax collection is included in the highly effective category. Because the result of billboard tax collection on local taxes has been less than 10%, the contribution of billboard tax to local taxes is included in the very low threshold.